Community preparedness for flood disasters: The role of knowledge and attitudinal factors in disaster-prone areas - Yahya, Ardiansyah Saifudin; Syahputra, Dicky Arya (Calamity: A Journal of Disaster Technology and Engineering, 2025)
Background: This research was conducted in Lebakharjo Village, Malang Regency. Malang Regency is prone to flooding due to high rainfall, with Lebakharjo Village being one of the affected areas. In July 2023, the village experienced another flood, damaging 119 houses and cutting off access to the village, leaving the village isolated. The purpose of this study was to assess the level of community preparedness in Lebakharjo Village for flood disasters. Methods: This study used a quantitative descriptive method with multiple correlation tests and multiple linear regression. Data collection was carried out by distributing questionnaires to respondents selected from flood-prone areas in Lebakharjo Village door to door. Findings: Data tabulation showed that 66 people, or 67.35%, were in the medium preparedness category, while 32 people, or 32.65%, were in the high preparedness category. This indicates the need for disaster preparedness training or evacuation simulations to improve community preparedness for floods. Knowledge and attitude significantly influence community preparedness in Lebakharjo Village for floods. The combined effect of Knowledge (X1) and Attitude (X2) variables on Community Preparedness (Y) is 28.5%, while the remaining 71.5% is influenced by other variables not covered in this study. Conclusion: This study highlights that increasing knowledge and attitudes through targeted interventions can improve flood preparedness in the Lebakharjo Village community. Novelty/Originality of this article: This study uniquely quantifies the impact of knowledge and attitudes on flood preparedness in the village, highlighting the need for targeted community training to improve preparedness.